A study into dentists’ knowledge of the treatment of traumatic injuries to young permanent incisors - M. N. KOSTOPOULOU & M. S. DUGGAL (Paediatric Dentistry, 2005)
The aims of this study were to evaluate dentists’ knowledge of the emergency treatment of traumatic injuries to young permanent incisors, and to investigate barriers to treatment.